2015
DOI: 10.1039/c5ra03029c
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of α-Fe2O3 films by electrodeposition and photodeposition of Co–Pi on them to enhance their photoelectrochemical properties

Abstract: Photocurrents of different structures of α-Fe2O3 photoanodes, prepared by calcination of electrodeposited α-Fe films, are enhanced by Co–Pi co-catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 36 publications
(63 reference statements)
1
25
0
Order By: Relevance
“…This onset shifted to smaller values in the case of Ti-doped hematite and shifted a bit further in the presence of ethanol. These values were about 100-200 mV smaller than the onset reported for chemical vapor deposited hematite [5], comparable with the values reported in other electrochemically deposited hematite studies [6,7], but larger than the onset potential reported for Pt doped, electrochemically deposited hematite photoanodes [8]. The most impressive changes were, however, recorded with the photocurrent.…”
Section: Current Voltage Data Obtained With Hematite Photoanodessupporting
confidence: 81%
See 3 more Smart Citations
“…This onset shifted to smaller values in the case of Ti-doped hematite and shifted a bit further in the presence of ethanol. These values were about 100-200 mV smaller than the onset reported for chemical vapor deposited hematite [5], comparable with the values reported in other electrochemically deposited hematite studies [6,7], but larger than the onset potential reported for Pt doped, electrochemically deposited hematite photoanodes [8]. The most impressive changes were, however, recorded with the photocurrent.…”
Section: Current Voltage Data Obtained With Hematite Photoanodessupporting
confidence: 81%
“…Thus, while for TiO 2 and WO 3 the hole diffusion length is $100 lm and 100-150 nm, respectively, in the case of hematite it is only 2-4 nm [6]. Furthermore, electron mobility in hematite is low (10 À1 V À1 s À1 ) [7] short [8]. For this reason, it is necessary to apply hematite on electrodes in the form of thin films, in order to allow charge carriers to reach the electrode.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Compared with other semiconductors such as single elements and sulfides, metal oxides have been widely concerned and studied because of their low cost and high stability. Among them, zinc oxide (ZnO) due to the low initial potential and the ability to quickly transfer electrons to stimulate more people to study it [7][8][9], Lei et al synthesized ZnO quantum dots and was employed to enhance H 2 evolution for triazine imide and graphitic carbon nitride (g-C 3 N 4 ) [10]. Moreover, Kang et al demonstrated that coating nafion polymer films on the surface of ZnO thin photoanode exhibited photoelectric properties [11].…”
Section: Introductionmentioning
confidence: 99%